Mechanism of action of a nitroimidazole-thiadiazole derivate upon Trypanosoma cruzi tissue culture amastigotes - Solange L. de Castro; Maria de Nazareth L. Meirelles (Memorias do Instituto Oswaldo Cruz, 1990)
Megazol (CL 64,855) a very effective drug in experimental infections by Trypanosoma cruzi, and also in in vitro assays with vertebrate forms of the parasite, had its parasite, had its activity upon macromolecule biosynthesis tested using tissue culture-derived amastigote forms. Megazol presented a drastic inhibition of [3H]-uridine incorporation, suggesting a selective activity upon protein synthesis. Comparing the three drugs, megazol was more potent than nifurtimox and benznidazole in inhibiting protein an DNA synthesis. Megazol showed a 91% of inhibition of [3H]-leucine incorporation whereas nifurtimox and benznidazole, 0% and 2%, respectively. These latter two drugs inhibited the incorporation of all the precursors tested at similar levels, but the concentration of benznidazole was always three times higher, suggesting different mechanisms of action or, more probably, a greater efficiency of the 5-nitrofuran derivate in relation to the 2-nitroimidazole. So, wes conclude that the mode of action of megazol is different from the ones of nifurtimox and benznidazole and that its primary effect is associated with an impairment of protein synthesis.